Asynchronous destruction of marsh and forest in Neolithic age: An example from Luotuodun site, Lower Yangtze - Deng, Zeyu; Ma, Chunmei; Wu, Li; Tan, Yan; Wang, Kunhua; Lin, Liugen; Zhao, Dongsheng; Shui, Tao; Zhu, Cheng (Frontiers in Earth Science, 2023)
The natural marshland and forest landscapes in the Lower Yangtze region have undergone a long history of human-induced destruction; however, little is known about the beginning and process of this destruction. In this study, we investigate the anthropogenic impact on the marsh and forest using cores collected from the vicinity of the Neolithic Luotuodun site, employing palaeoenvironmental and palaeovegetation methods. Our results indicate that the marsh was disturbed by the Neolithic community at 7500 cal yr BP and was completely destroyed at 6500 cal yr BP. Deforestation began at 6500 cal yr BP, and the original mixed broadleaf evergreen and deciduous forest was completely cleared at 4800 cal yr BP. Our findings demonstrate that the Neolithic community in the Luotuodun site prioritized the transformation of marsh in low-lying areas before deforestation. Given that most recent research has focused on pollen-based forest dynamics to study terrestrial landscape changes, the emergence and evolution of anthropogenic landscapes may be greatly underestimated.